Mindfulness and Nutrition in College Age Students - Stephanie Bryan (Journal of Basic & Applied Sciences, 2016)
Primary Objective: The obesity rate among young Americans is now almost 25% with higher rates found in minority populations; lack of exercise and poor eating habits are some of the leading causes. The collegiate environment provides a unique opportunity to share nutrition-related knowledge while enhancing students’ awareness,both of which may ultimately lead to changes in health-related behaviors. Mindful eating is associated with a lower Body Mass Index (BMI) and an increased intake of fruits and vegetables. A semester-long nutrition course may result in an increased awareness of eating patterns and may be associated with improvements in dietary intake over time. Methods: Of the 38 students registered for a college-level nutrition course held during an almost four-month-long-semester, 37 self-selected to complete an anonymous Mindful Eating Questionnaire (MEQ) before and after taking the nutrition course; the participants also answered two open-ended questions for qualitative data collection post-test. Results: Of the 37 students 22 were female and 16 male between the ages of 18 and 24; 35 % self-identified as African American, 29% self-identified as white, 22% as self-identified as Latino/Hispanic, 10% self-identified as other and 2% self-identified as Native Hawaiian or Pacific Islander. No significant change in the MEQ score occurred from pre to post-test; however, there was a trend towards improvement. The students’ answers to open-ended questions regarding any shifts in understanding, approach, or changes in eating habits, revealed overwhelming increases in mindful eating and dietary changes Conclusions: A collegiate course taught over a semester is a unique opportunity to introduce nutrition information, emphasizing the connection between nutrition, optimal health, and disease prevention. A student’s exposure to nutrition information while also observing their own eating patterns over time can provide a non-judgmental informed space that allows for the development of a heightened awareness. In turn, the heightened awareness can lead to changes in eating behaviors as evidenced here.